2013
DOI: 10.1016/j.bcp.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of constitutive aryl hydrocarbon receptor (AhR) signaling attenuates androgen independent signaling and growth in (C4-2) prostate cancer cells

Abstract: The aryl hydrocarbon receptor is a member of the basic-helix-loop-helix family of transcription factors. AhR mediates the biochemical and toxic effects of a number of polyaromatic hydrocarbons such as 2,3,7,8,-tetrachloro-dibenzo-p-dioxin (TCDD). AhR is widely known for regulating the transcription of drug metabolizing enzymes involved in the xenobiotic metabolism of carcinogens and therapeutic agents, such as cytochrome P450-1B1 (CYP1B1). Additionally, AhR has also been reported to interact with multiple sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 72 publications
(61 reference statements)
2
27
0
2
Order By: Relevance
“…We have previously reported that AhR is required to maintain hormone independent signaling and growth by the androgen receptor in C4-2 prostate cancer cells. This evidence shows a direct role for AhR in androgen receptor dependent growth of prostate cancer cells [29]. In this present study we show that AhR is constitutively active in advanced prostate cancer cells and that ablation of constitutive AhR signaling to inhibit androgen independent growth is not dependent on androgen receptor status.…”
Section: Introductionsupporting
confidence: 68%
“…We have previously reported that AhR is required to maintain hormone independent signaling and growth by the androgen receptor in C4-2 prostate cancer cells. This evidence shows a direct role for AhR in androgen receptor dependent growth of prostate cancer cells [29]. In this present study we show that AhR is constitutively active in advanced prostate cancer cells and that ablation of constitutive AhR signaling to inhibit androgen independent growth is not dependent on androgen receptor status.…”
Section: Introductionsupporting
confidence: 68%
“…There is evidence that AhR ligands are antiandrogenic in AR-expressing prostate cancer cells, and the AhR itself is growth inhibitory (Gluschnaider et al 2010). In contrast, knockdown of the AhR in AR-negative prostate cancer cells decreases proliferation (Tran et al 2013), multiple AhR ligands induce pro-invasion MMP9 (Haque et al 2005), and the AhR antagonist CH223191 inhibits growth (Richmond et al 2014). In TRAMP mice which are AR-positive, the evidence suggests that the AhR and its ligands are tumor growth inhibitory, although some mixed results were observed for TCDD (Fritz et al 2007; Fritz et al 2009; Moore et al 2016).…”
Section: The Ahr and Its Ligand In Tumorigenesis And Cancer Chemotherapymentioning
confidence: 99%
“…However, AhR nuclear localization and transcriptional activity is clearly increased in TNBC in suspension culture, and other recent studies find that AhR affects growth and migration of breast cancer cells [27, 28] and castrate-resistant prostate cancer cells [46]. Studies examining AhR expression in breast cancer primary tumors found that higher AhR expression correlates with good prognosis [47].…”
Section: Discussionmentioning
confidence: 99%